Concomitant Use of Psychotropic Medication With Stimulants for the Treatment of ADHD in Children and Adolescents: A Retrospective Insurance Claims Study in the United States. Issue 2 (January 2020) - Zhou, Zhou; Betts, Keith A.; Bocharova, Iryna; Kinrich, David; Spalding, William M.
Objective: To evaluate annual concomitant psychotropic medication use among stimulant-treated children/adolescents with ADHD.Method: Children/adolescents with ≥1 primary ADHD diagnosis who had received ≥30 days of stimulant medication were identified from insurance claims for each calendar year (2011-2014). Use of 15 psychotropic medications concomitantly with stimulants was evaluated and their prevalence in each year was calculated overall and by medication category for children (6-12 years) and adolescents (13-17 years).Results: Each year 133, 354 to 157, 303 children and 95, 632 to 111, 280 adolescents were included. Annual period prevalence of any concomitant psychotropic medication use was 22.9% to 25.0% for children and 25.2% to 28.2% for adolescents. The most common medication categories included selective serotonin reuptake inhibitors (children: 6.8%-7.9%; adolescents: 12.7%-14.9%), atypical antipsychotics (4.2%-5.4%; 5.3%-6.3%), and guanfacine extended release (5.1%-7.0%; 2.3%-3.6%).Conclusion: Around a quarter of children/adolescents with ADHD were prescribed psychotropic medication concomitant to stimulant treatment, although only 2 of the 15 medication classes studied were Food and Drug Administration (FDA)-approved for adjunctive use.